A nitrogen heterocyclic polyether and its preparation method and application
By using the preparation method of azelocyclic polyether in the aldehyde-free adhesive, the problem of slow curing speed of the aldehyde-free adhesive is solved, the curing speed and the strength of the aldehyde-free plate are improved, and a more efficient production process is achieved.
Patent Information
- Application Number
- CN202211568569.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-08
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-12-08
AI Technical Summary
The curing speed of existing aldehyde-free adhesives is slow, which limits production efficiency. When the curing speed is too fast, curing begins at the glue-applying stage, which is not conducive to subsequent hot pressing operations.
Using the preparation method of azoheterocyclic polyether, the preparation of azoheterocyclic polyether is improved in the presence of a catalyst by using azoheterocyclic and ethylene oxide as raw materials in a kettle reactor, and the curing speed is increased, and it is used in artificial board adhesives.
It effectively improves the curing speed of the adhesive and the strength of the aldehyde-free plate, solving the problems of slow curing speed and difficult construction.
Smart Images

Figure BDA0003987088770000021 
Figure BDA0003987088770000022 
Figure BDA0003987088770000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of organic synthesis and adhesives, and specifically relates to a preparation method of nitrogen heterocyclic polyether and application thereof. Background Art
[0002] At present, the commonly used synthetic adhesives for artificial boards are formaldehyde-based adhesives, including "trialdehyde adhesives" represented by urea-formaldehyde resins, phenolic resins and melamine-formaldehyde resins. These three types of adhesives all use formaldehyde as a synthetic raw material. Formaldehyde escapes from adhesive products during production and use, which is regarded as one of the main sources of indoor air pollution. The pollution cycle is long and difficult to remove fundamentally.
[0003] Due to environmental considerations, formaldehyde-free adhesives have been increasingly used in recent years. Its main component is polyisocyanate, and tertiary amine is used as a crosslinker or curing agent. Its biggest advantage is that it does not contain formaldehyde, and can use materials such as straw as a base material, which is environmentally friendly. In addition, it also has the advantages of high bonding strength and low adhesive dosage.
[0004] At present, isocyanate formaldehyde-free adhesives mainly use tertiary amines such as triethanolamine, diethanol triisopropanolamine, and monoethanol diisopropanolamine as curing agents. Although the introduction of formaldehyde is avoided, compared with formaldehyde-containing adhesives such as phenolic resins, there is still a problem of slow curing speed. The curing speed of the former at 100°C is about 30s slower than that of the latter, which limits the production efficiency to a certain extent. This is also an unfavorable factor for the further promotion of formaldehyde-free adhesives.
[0005] In order to increase the curing speed of isocyanate-based formaldehyde-free adhesives, the conventional solution is to add trace amounts of highly active primary and secondary amines such as ethanolamine and diethanolamine to the curing agent. However, the introduction of highly active primary and secondary amines will cause the curing speed to be too fast, and curing will begin at the gluing stage, which is not conducive to subsequent hot pressing operations.
[0006] Therefore, it is necessary to develop an adhesive that can be used in the production of formaldehyde-free artificial boards, and the adhesive has the characteristics of fast curing speed and easy construction. Summary of the invention
[0007] In view of the problem that the curing speed of curing systems such as ethanolamine in the prior art is slow, the purpose of the present invention is to provide a preparation method of nitrogen heterocyclic polyether and its application in artificial board adhesives. The nitrogen heterocyclic polyether can effectively increase the curing speed, and the strength of the prepared artificial board is improved compared with the triethanolamine curing system.
[0008] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows:
[0009] A method for synthesizing an azoheterocyclic polyether, the method comprising the following steps:
[0010] S1: In a tank reactor, nitrogen heterocycle and EO are used as raw materials to prepare nitrogen heterocycle polyether in the presence of a catalyst;
[0011] In the present invention, the S1 preferably adopts a kettle type semi-batch process.
[0012] In the present invention, in S1, the nitrogen heterocyclic initiator is at least one of the following structures:
[0013]
[0014] In the present invention, the catalyst in S1 is preferably water, caustic soda, aqueous solution of quaternary ammonium alkali, etc., and water is more preferred. The amount of catalyst is 1-50% of the mass of the initiator, preferably 5-10%.
[0015] In the present invention, the reaction temperature of S1 is 80 to 150°C, preferably 90 to 130°C, and more preferably 100 to 120°C;
[0016] EO feed space velocity is 1~50g EO / g cat / h -1 , preferably 10 to 20 g EO / g cat / h -1 .
[0017] In the present invention, the EO grafting number is controlled by controlling the EO feed amount, preferably the grafting number is ≤50, more preferably the grafting number is 5 to 10, and the structure of the prepared nitrogen heterocyclic polyether is as follows:
[0018]
[0019] The grafting number is x (e.g., B) or x+y (e.g., F) or x+y+z (e.g., A);
[0020] The nitrogen heterocyclic polyethers A to F have a molecular weight of 80 to 2300, preferably a molecular weight of 200 to 1000, a nitrogen content of ≥1 wt%, preferably 2 to 15 wt%, and an oxygen content of >10 wt%, preferably 20 to 40 wt%.
[0021] The present invention also relates to the application of the nitrogen heterocyclic polyether in an adhesive for artificial boards.
[0022] An adhesive for artificial boards, comprising component A and component B, wherein component A contains the above-mentioned nitrogen heterocyclic polyether, and specifically, component A is obtained by diluting the nitrogen heterocyclic polyether with a diluent, the diluent is preferably water, and the water content after dilution is 1 to 50 wt%, preferably 10 to 25 wt%;
[0023] Component B is polymethylene polyphenyl polyisocyanate, and the polyisocyanate functionality is ≥2;
[0024] The mass ratio of the component A to the component B is 1:1 to 1:100, preferably 1:10 to 1:50.
[0025] The present invention also relates to the application of the above-mentioned artificial board adhesive in the preparation of formaldehyde-free boards.
[0026] In one embodiment, the preparation of the formaldehyde-free board includes: mixing component A and component B with a wood-based board substrate, and hot pressing the mixture into a board;
[0027] The substrate is preferably wood shavings or straw shavings;
[0028] The amount of A+B component relative to the substrate (sizing amount) is 1-10wt%, preferably 2-5wt%; the hot pressing temperature is 200-280°C, preferably 220-240°C; the hot pressing factor is 2-10s / mm, preferably 3-5s / mm;
[0029] Finally, a formaldehyde-free board with a size of, for example, 600*600*10 mm is obtained.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] On the one hand, nitrogen heterocyclic initiators have a higher nitrogen content and a higher tertiary amine concentration per unit mass than olamine initiators, which can provide more catalytic centers for curing and help improve the curing rate. On the other hand, five-membered and six-membered nitrogen heterocyclic rings are more rigid than chain olamine molecules, which is beneficial to improve the strength of formaldehyde-free boards. By grafting a certain amount of EO to the nitrogen heterocyclic initiator, it is beneficial to disperse the nitrogen heterocyclic ring in polymethylene polyphenyl polyisocyanate and improve the catalytic effect, but too high a proportion of EO will dilute the concentration of nitrogen heterocyclic rings in disguise, so the number of EO grafts needs to be kept within a certain range.
[0032] The nitrogen heterocyclic polyether of the present invention can effectively improve the curing speed of the adhesive and the strength of the formaldehyde-free board. DETAILED DESCRIPTION
[0033] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0034] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0035] Source of raw materials:
[0036]
[0037] Test method:
[0038] The internal bonding strength and static bending strength of the plate shall be implemented in accordance with the national standard GB / T 17657-2013.
[0039] Example 1
[0040] S1: 87 g of tripiperazine (starter a) and 4.35 g of water were placed in a 1 L reactor at room temperature. The atmosphere was replaced with 1 MPa nitrogen for 3 times, and then nitrogen was added until the pressure in the reactor was 0.5 MPa. The temperature was raised at 2 °C / min until the internal temperature reached 100 °C. Then, a plunger pump was used to feed the mixture at a feed space velocity of 20 h. -1 Feed ethylene oxide and maintain the reaction temperature at 100° C. When the ethylene oxide feed reaches 440 g, stop feeding and maintain the reaction at 100° C. for 1 h.
[0041] S2: After the reaction is completed, the pressure is released and the gas in the kettle is replaced with 1 MPa nitrogen for 3 times. After cooling to 80°C, 25 g of water is added to the kettle, stirred for 5 min, and filtered while hot to obtain component A1.
[0042] S3: 2kg wood shavings, 0.8g A1 component, 39.2g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 240°C, and the hot pressing factor was 4s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.61MPa and the static bending strength was 16.7MPa.
[0043] Example 2
[0044] S1: 130 g hydroxyethylpiperazine (starter b) and 7.8 g water were placed in a 1 L reactor at room temperature. The atmosphere was replaced with 1 MPa nitrogen for 3 times. Then nitrogen was added until the pressure in the reactor reached 0.5 MPa. The temperature was raised at 2 °C / min until the internal temperature reached 120 °C. Then, a plunger pump was used to feed the mixture at a space velocity of 20 h. -1 Feed ethylene oxide and maintain the reaction temperature at 120° C. When the ethylene oxide feed amount reaches 176 g, stop feeding and maintain the reaction at 120° C. for 1 hour.
[0045] S2: After the reaction, the pressure was released and the gas in the kettle was replaced with 1 MPa nitrogen for 3 times. After cooling to 80°C, 15 g of water was added to the kettle, stirred for 5 min, and filtered while hot to obtain component A2.
[0046] S3: 2kg wood shavings, 6.3g A2 component, 93.8g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 235°C, and the hot pressing factor was 3.5s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.75MPa and the static bending strength was 16.3MPa.
[0047] Example 3
[0048] S1: 129g aminoethylpiperazine (starter c) and 9g water were placed in a 1L reactor at room temperature. The atmosphere was replaced with 1Mpa nitrogen for 3 times, and then nitrogen was added to the reactor until the pressure was 0.5MPa. The temperature was raised at 2℃ / min until the internal temperature reached 115℃. Then, the plunger pump was used to feed the mixture at a feed space velocity of 20h. -1 Feed ethylene oxide and maintain the reaction temperature at 115°C. When the ethylene oxide feed reaches 220 g, stop feeding and maintain the reaction at 115°C for 1 hour.
[0049] S2: After the reaction is completed, the pressure is released and the gas in the kettle is replaced with 1Mpa nitrogen for 3 times. After cooling to 80°C, 20g of water is added to the kettle, stirred for 5 minutes and filtered while hot to obtain component A3.
[0050] S3: 2kg wood shavings, 4.0g A3 component, 62g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 240°C, and the hot pressing factor was 4s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.58MPa and the static bending strength was 16.9MPa.
[0051] Example 4
[0052] S1: 87 g of morpholine (starter d) and 6.96 g of water were placed in a 1 L reactor at room temperature. The atmosphere was replaced with 1 MPa nitrogen three times, and then nitrogen was added to the reactor until the pressure was 0.5 MPa. The temperature was raised at 2 °C / min until the internal temperature reached 118 °C. Then, a plunger pump was used to feed the mixture at a space velocity of 20 h. -1 Feed ethylene oxide and maintain the reaction temperature at 118° C. When the ethylene oxide feed amount reaches 132 g, stop feeding and maintain the reaction at 118° C. for 1 hour.
[0053] S2: After the reaction, the pressure was released and the gas in the kettle was replaced with 1 MPa nitrogen for 3 times. After cooling to 80°C, 22 g of water was added to the kettle, stirred for 5 min, and filtered while hot to obtain component A4.
[0054] S3: 2kg wood shavings, 7.3g A4 component, 72.7g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 220°C, and the hot pressing factor was 3s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.49MPa and the static bending strength was 17.1MPa.
[0055] Example 5
[0056] S1: 73 g of oxazolidine (starter e) and 6.6 g of water were placed in a 1 L reactor at room temperature. The atmosphere was replaced with 1 MPa nitrogen for 3 times, and then nitrogen was added until the pressure in the reactor was 0.5 MPa. The temperature was raised at 2 °C / min until the internal temperature reached 109 °C. Then, a plunger pump was used to feed the reactor at a feed space velocity of 20 h. -1 Feed ethylene oxide and maintain the reaction temperature at 109° C. When the ethylene oxide feed reaches 88 g, stop feeding and maintain the reaction at 109° C. for 1 h.
[0057] S2: After the reaction is completed, the pressure is released and the gas in the kettle is replaced with 1 MPa nitrogen for 3 times. After cooling to 80°C, 10 g of water is added to the kettle, stirred for 5 min, and filtered while hot to obtain component A5.
[0058] S3: 2kg wood shavings, 4.3g A5 component, 55.7g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 225°C, and the hot pressing factor was 4.5s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.46MPa and the static bending strength was 17.2MPa.
[0059] Example 6
[0060] S1: 72g of tetrahydroimidazole (starter f) and 7.2g of water were placed in a 1L reactor at room temperature. The atmosphere was replaced with 1Mpa nitrogen for 3 times, and then nitrogen was added until the pressure in the reactor was 0.5MPa. The temperature was raised at 2℃ / min until the internal temperature reached 105℃. Then, the temperature was raised by a plunger pump at a feed space velocity of 20h -1 Feed ethylene oxide and maintain the reaction temperature at 105° C. When the ethylene oxide feed amount reaches 396 g, stop feeding and maintain the reaction at 105° C. for 1 hour.
[0061] S2: After the reaction, the pressure was released and the gas in the kettle was replaced with 1 MPa nitrogen for 3 times. After cooling to 80°C, 13 g of water was added to the kettle, stirred for 5 min, and filtered while hot to obtain component A6.
[0062] S3: 2kg wood shavings, 1.1g A5 component, 38.9g B component (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 230°C, and the hot pressing factor was 5s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. After pressing and cooling to room temperature, a strength test was performed. After testing, the internal bonding strength of the board was 0.65MPa and the static bending strength was 16.7MPa.
[0063] Comparative Example 1
[0064] Comparative Example 1: 85% triethanolamine aqueous solution was directly used as a curing agent and combined with component B to prepare a formaldehyde-free board. 2kg of wood shavings, 7.3g of curing agent, and 72.7g of component B (polymethylene polyphenyl polyisocyanate) were placed in a stirrer, stirred at room temperature for 10 minutes, and then transferred to a mold for hot pressing. The hot pressing temperature was 220°C, and the hot pressing factor was 5s / mm. A formaldehyde-free board with a size of 600*600*10mm was obtained. The internal bonding strength of the board was tested to be 0.31MPa, and the static bending strength was 14.5Mpa.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is that the initiator of component A is triethanolamine, component A is prepared by the method of Example 1, and mixed with component B to make a board. The hot pressing factor of the board is 5.7s / mm. The internal bonding strength of the board is tested to be 0.45MPa, and the static bending strength is 13.8MPa.
[0067] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A nitrogen heterocyclic polyether, characterized in that The structure is as follows: The average EO grafting number x+y+z in the nitrogen heterocyclic polyether is ≤50; the molecular weight of the nitrogen heterocyclic polyether is 80-2300, the nitrogen content is ≥1wt%, and the oxygen content is >10wt%.
2. The nitrogen heterocyclic polyether according to claim 1, wherein The average EO grafting number x+y+z in the nitrogen heterocyclic polyether is 5 to 10; the molecular weight of the nitrogen heterocyclic polyether is 200 to 1000, the nitrogen content is 2 to 15 wt%, and the oxygen content is 20 to 40 wt%.
3. The method for preparing the nitrogen heterocyclic polyether according to claim 1 or 2, comprising: The product is prepared with an initiator and EO as raw materials in the presence of a catalyst.
4. The method according to claim 3, wherein: A kettle type semi-batch process is adopted.
5. The method according to claim 3 or 4, wherein: The catalyst is selected from water, caustic soda, and quaternary ammonium base.
6. The method according to claim 5, wherein: The amount of the catalyst used is 1 to 50% of the mass of the initiator.
7. The method according to claim 3 or 4, wherein: Control the EO grafting number ≤50.
8. The method according to claim 7, wherein: The number of EO grafting is controlled to be 5 to 10.
9. An adhesive for artificial boards, comprising component A and component B, wherein: Component A contains the nitrogen heterocyclic polyether according to claim 1 or 2; The mass ratio of component A to component B is 1:1 to 1:
100.
10. The artificial board adhesive according to claim 9, wherein: The mass ratio of component A to component B is 1:10 to 1:
50.
11. The artificial board adhesive according to claim 9, wherein: The component A is a mixture of nitrogen heterocyclic polyether and water, and the water content is 1-50 wt %.
12. The artificial board adhesive according to claim 11, wherein: The water content in the component A is 10-25 wt%.
13. The artificial board adhesive according to claim 9 or 10, wherein: Component B is polymethylene polyphenyl polyisocyanate.
14. Use of the artificial board adhesive according to any one of claims 9 to 13 in the preparation of formaldehyde-free boards.
15. The use according to claim 14, wherein: The glue application amount is 1-10wt%; the hot pressing temperature is 200-280°C; and the hot pressing factor is 2-10s / mm.
16. The use according to claim 15, wherein: The glue application amount is 2-5wt%; the hot pressing temperature is 220-240°C; and the hot pressing factor is 3-5s / mm.
Citation Information
Patent Citations
Aldehyde-free artificial board adhesive and aldehyde-free artificial board produced by same
CN109081902A
Composition, adhesive combined material of composition, formaldehyde-free artificial board and preparation method of formaldehyde-free artificial board
CN115141343A